Does Cooperative Learning Bring Positive Effect on Students’ Vocabulary Achievement? - Nur Hidayat; Eva Puspita Sari (Institut Agama Islam Negeri Palopo, 2019)
This study wanted to investigate the effect of cooperative learning on students’ vocabulary achievement. The subject of this study is 54 students of grade seven in one of public junior high schools in East Java Indonesia. The researcher divided the subjects into two groups; experimental and control groups which consisted of 27 students. The instruments of this study were used tests, and observation. The tests consisted of pre and posttest which delivered in the first and the last meeting. The observation was done to observe the situation of students in the classroom during the implementation of cooperative learning and conventional method. In this study, the researcher used SPSS 24 to analyze the data. The result of this study revealed that the use of cooperative learning and conventional method significantly improve students’ vocabulary achievement. It also gave positive effects for the students such as; increasing students’ motivation and cooperation and decreasing their nervous. The result also showed that there was no significant different between conventional method and cooperative learning on students’ vocabulary achievement.